X

(2x + 13) : 4 = (6x - 30) . 2

Answers
x=11/2It requires explanation and i dont want to solve this question you will solve it using your own mind but i can give examples and explanation
umairml
21 January 2019
(2x+13):4 =(6x-30):2means (2x+13)/4 = (6x-30)/2implies (2x+13)*2 =(6x-30)*4implies 4x +26 = 24x - 120implies 120+26 = 24x-4ximplies 20x = 146implies x = 146/20 = 7.3therefore x = 7.3
prameela
22 January 2019
2(2x+13)=4(6x-30)4x+26=24x-120120+26=24x-4x146=20xx=146/20=7.3
anu
22 January 2019
multiplying out the brackets on both sides we get8x+52=12x-60bringing the xs to one side, we get:112=4xx = 28
prashasti
29 January 2019
Applying BODMAS  rule(2x + 13)*4 = (6x-30)*28x + 52 = 12x -60;taking variable to R.H.S112 = 4x;x = 112/4;x = 28
ashish1304
04 February 2019
As the LHS equation is in the form ratio, move that 4 to RHS2x+13=(6x-30).2.42x+13=48x-240253=46xx=5.5
navya
15 March 2019
2x+13=(6x-30).2.42x+13=48x-240253=46xx=5.5
laksh
25 March 2019
Add an answer Cancel reply

Similar questions